Old Mutual : breaking into the mass market - Maunder, Peta Krost; Chinje, Nathalie (London : SAGE Publications Ltd, 2017)
It was November 2014 and just three months since Old Mutual, a well-established, global financial services group, had launched the 2-in-One Savings product to target the South African retail mass market. Anele Mbuya, senior marketing actuary for Old Mutuals Retail Mass Market, wondered whether the products marketing strategy needed to be revitalised for it to achieve the sales forecasts for the next operating period. However, a tight marketing budget, customer perceptions of Old Mutual as a life insurer rather than a savings company and a poor savings culture in South Africa were some of the challenges the organisation faced. Old Mutual had a good track record in developing and implementing marketing strategies aimed at multiple market segments. However, it had still not optimally serviced the retail mass market. Mbuya had to consider how to take advantage of the opportunities this segment presented, and how to address its challenges for the product to achieve its potential.
Originally published: Krost Maunder, P., & Chinje, N. (2015). Old Mutual: Breaking into the Mass Market. WBS-2015-8. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Old Mutual (Firm); Financial services industry -- South Africa -- Case studies; Asset management accounts -- South Africa -- Case studies